Surrogate-assisted reliability-based design optimization of PEMFC serpentine flow channel - Abebe, Misganaw; Koo, Bonyong; Kim, Min-Geun; Kim, Hyun-Seok (Frontiers in Energy Research, 2024)
In a fuel cell, flow channels are crucial components responsible for various essential functions that enable the system to operate effectively. The design of a directly coupled flow channel in a Proton Exchange Membrane Fuel Cell (PEMFC) system, assuming deterministic parameters, has been extensively studied. However, this deterministic approach neglects the inherent uncertainties in system performance during real-life operation, resulting in potentially unreliable and suboptimal performance. To address this issue, we propose a reliability-based design optimization (RBDO) of the PEMFC’s channel structure, considering uncertainties in operating parameters. This paper presents a numerical model of the PEMFC in COMSOL, deterministic designs, reliability-based designs and a global sensitivity analysis on the PEMFC cell’s potential output and average water activity on the membrane. Although the RBDO approach shows a reduction in cell efficiency compared to the deterministic design, it significantly improves reliability, with increases from 60.92% to 95.10% for cell potential and from 79.31% to 96.85% for water activity.